COST, ACCESS, AND QUALITY IN ONLINE NURSING AND ALLIED HEALTH PROFESSIONS - Tracy Wright; Linda Thompson (Online Learning, 2019)
Northwest Technical College researched, planned for, and has successfully implemented a unique delivery of its Practical Nursing Program through the use of Internet technology. This Distance Practical Nursing exploratory paper presents a historical overview of the program, assesses job market needs in the field of nursing, evaluates use of varying delivery methodologies, outlines program successes, and identifies barriers to distance delivery of this health curriculum. The essential components of quality, access, and cost are highlighted and related to the unique challenges they present in the field of distance education.